Researching the English Reformation : Essays in Honour of W.B. Patterson - Engel,William E.; Guyer, Benjamin M. (Anglican-Episcopal Theology and History, 2025)
Researching the Reformation studies the history and historiography of early Anglicanism in order to pay tribute to the scholarship of W. Brown Patterson. Three of the volume's sections are inspired by Patterson's research monographs. The first taking its cue from Patterson's study of Thomas Fuller, analyses the intersection of mythology and historiography surrounding the English Reformation. The second, following Patterson's study of William Perkins, turns to the general theological and political contours of early modern England. The third pans out in both geography and chronology, thus emulating Patterson's award-winning study of King James VI and I. The fourth and final section analyses how, in the nineteenth century, the early modern period was reinvented by the Parker Society and the Oxford Movement. Contributors are: Benjamin M. Guyer, William E. Engel, George Core, George Poe, Diarmaid MacCulloch, Anthony Milton, James Ross MacDonald, Scott Kindred-Barnes, Paul Dominiak, David Neelands, John N. Wall, Torrance Kirby, Margo Todd, Nicholas Tyacke, Lori Anne Ferrell, and Peter Nockles.